Corpus-based approaches to register variation - Seoane, Elena; Biber, Douglas (Studies in corpus linguistics ;, 2021)
"As the first collective volume to focus exclusively on corpus-based approaches to register variation, this book provides an exhaustive account of the range and depth of possibilities that the domain of register variation in English has to offer. It illustrates register variation analysis in different theoretical frameworks, such as Probabilistic Grammar, Systemic Functional Linguistics, and Information Theory, and proposes a new framework within the Text Linguistic Approach: the continuous-situational analytical framework. Several of the contributions apply Multi-Dimensional Analysis to corpus data in order to unveil register (dis)similarities, while others rely on logistic regression models and periodization techniques based on Kullback-Leibler divergence. The volume includes both inter-register and intra-register variation analysis of a wide spectrum of varieties, speakers and periods: British and American English, learner varieties, L2 varieties, and EFL, and also contains diachronic studies covering early and late Modern English. This broad scope should be a source of inspiration for anyone interested in historical and ongoing register variation in a vast range of varieties of English worldwide"--